Lifestyle trajectories in middle-aged adults and their relationship with health indicators - Roca-Ventura, Alba; Solana-Sánchez, Javier; Cattaneo, Gabriele; Tormos-Muñoz, Josep M.; Pascual-Leone, Álvaro; Bartrés-Faz, David (Frontiers in Public Health, 2024)
Understanding the impact of diverse lifestyles on health preservation and disease risk is crucial for effective interventions. In this study, lifestyle engagement over five years was analyzed in 3,013 healthy adults aged 40-70 from the Barcelona Brain Health Initiative using K-means clustering. Nine modifiable risk factors were considered, including cognitive, physical, and social activity, vital plan, diet, obesity, smoking, alcohol consumption, and sleep. The data-driven analysis classified subjects into five lifestyle profiles, revealing associations with health behaviors and risk factors. Those exhibiting high scores in health-promoting behaviors and low-risk behaviors, demonstrate a reduced likelihood of developing diseases (p<0.001). In contrast, profiles with risky habits showed distinct risks for psychiatric, neurological, and cardiovascular diseases. Participant's trajectories in lifestyles remained relatively stable over time. Data-driven insights emphasize the importance of maintaining a healthy lifestyle, informing personalized interventions to enhance health outcomes in an aging society.